2008
DOI: 10.1029/2007jd009157
|View full text |Cite
|
Sign up to set email alerts
|

Impact of variations in solar activity on hydrological decadal patterns in northern Italy

Abstract: [1] Using spectral and statistical analyses of discharges and basin average precipitation rates acquired over the Po River since the early 1800s, we investigate the impact of variations in solar activity on hydrological decadal patterns over northern Italy. Wet and dry periods appear to alternate in accordance with polarized sunspot cycles. Intriguingly, a solar signature on Po River discharges is detected to be highly significant since the late 1800s, before the onset of sunspots hyperactivity established by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
59
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 79 publications
(75 reference statements)
7
59
1
Order By: Relevance
“…Sonett and Suess (1984) described a significant cycle in solar activity around ∼ 208 years (Suess solar cycle), which could have triggered our ∼ 200-year cyclicity. The observed ∼ 240-year periodicity in the Padul-15-05 record could be either related to variations in solar activity or due to the mixed effect of the solar cycle together with the ∼ 300-year NAO-interpreted cycle and could point to a solar origin of the centennialscale NAO variations as suggested by previously published research (Lukianova and Alekseev, 2004;Zanchettin et al, 2008). Finally, a significant ∼ 170-year cycle has been observed in both the Mediterranean forest taxa and Botryococcus times series from the Padul-15-05 record.…”
Section: Centennial-scale Variabilitymentioning
confidence: 70%
“…Sonett and Suess (1984) described a significant cycle in solar activity around ∼ 208 years (Suess solar cycle), which could have triggered our ∼ 200-year cyclicity. The observed ∼ 240-year periodicity in the Padul-15-05 record could be either related to variations in solar activity or due to the mixed effect of the solar cycle together with the ∼ 300-year NAO-interpreted cycle and could point to a solar origin of the centennialscale NAO variations as suggested by previously published research (Lukianova and Alekseev, 2004;Zanchettin et al, 2008). Finally, a significant ∼ 170-year cycle has been observed in both the Mediterranean forest taxa and Botryococcus times series from the Padul-15-05 record.…”
Section: Centennial-scale Variabilitymentioning
confidence: 70%
“…Signals of solar activity have recently been found with spectral analysis techniques in the river Nile by Ruzmaikin et al (2006), who found a low-frequency 88-year variation present in solar variability and in the Nile records. Similarly, Zanchettin et al (2008) found that the discharge of the Po river appear to be correlated with variations in solar activity, on decadal time scales.…”
Section: Introductionmentioning
confidence: 94%
“…Log-log plot of F (s) versus s for original streamflow and sunspot data sets by using DFA method (Figure ( [15,81]. Moreover, cycle of solar activity represented by sunspot is one of most robust effect which affects on streamflow fluctuations.…”
Section: Mf-dxa Of Sunspots and River Flow Fluctuationsmentioning
confidence: 99%